Secukinumab in Hidradenitis Suppurativa Patients Who Failed Adalimumab: A 52-Week Real-Life Study - Martora F; Marasca C; Cacciapuoti S; Fariello F; Potestio L; Battista T; Scalvenzi M; Megna M (Dove Medical Press, 2024)
Fabrizio Martora,1 Claudio Marasca,2 Sara Cacciapuoti,1 Federica Fariello,1 Luca Potestio,1 Teresa Battista,1 Massimiliano Scalvenzi,1 Matteo Megna1 1Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy; 2Dermatology Unit, Medical Department, "Antonio Cardarelli" National Hospital, Naples, ItalyCorrespondence: Fabrizio Martora, Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Naples, 80131, Italy, Tel +39 - 081 - 7462457, Fax +39 - 081 - 7462442, Email fabriziomartora92@libero.itBackground: The treatment of hidradenitis suppurativa (HS) has always been a real challenge for dermatologists; to date, adalimumab the only biologic drug approved for HS is adalimumab, an anti-tumor necrosis factor (TNF)-α drug, the approval of this drug dates to 2015, data provided by real life show an effectiveness rate of about 60% percent. Recently (31 October 2023) FDA approves secukinumab for moderate-severe HS. The treatment and management of HS is very challenging as available treatments are very limited and show very variable outcomes.Methods: We conducted a prospective monocentric study designed to evaluate the efficacy and safety of secukinumab treatment in HS patients in a real-life setting.Results: The initial cohort of patients recruited included 21 HS patients including 12 females and 9 males. About 57.1% of patients achieved the primary endpoint and recorded significant decrease in all the severity assessment scales (IHS4, DLQI and VAS pain scale) at week 16 and 52, when HiSCR reached 71.4%.Conclusion: The results of our study highlight that treatment with secukinumab in patients with severe HS who failed adalimumab may be a safe and effective therapeutic weapon.Keywords: hidradenitis suppurativa, secukinumab, adalimumab, treatments